2017
DOI: 10.1016/j.cell.2017.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Patterns of De Novo Mutation in Simplex Autism

Abstract: SUMMARY To further our understanding of the genetic etiology of autism, we generated and analyzed genome sequence data from 516 idiopathic autism families (2,064 individuals). This resource includes >59 million single-nucleotide variants (SNVs) and 9,212 private copy number variants (CNVs), of which 133,992 and 88 are de novo mutations (DNMs), respectively. We estimate a mutation rate of ~1.5×10−8 SNVs per site per generation with a significantly higher mutation rate in repetitive DNA. Comparing probands and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
356
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(377 citation statements)
references
References 77 publications
(130 reference statements)
19
356
2
Order By: Relevance
“…Collectively, this catalogue of de novo SVs achieved high specificity, almost certainly at the cost of sensitivity for SV detection from short-read WGS, though there are few gold-standard datasets to estimate accurate SV mutation rates at present. Notably, a study from Turner et al published during revision of this manuscript identified 88 de novo SVs from 476 of these quartets with an estimated 87.5% confirmation rate using microarray validation 31 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Collectively, this catalogue of de novo SVs achieved high specificity, almost certainly at the cost of sensitivity for SV detection from short-read WGS, though there are few gold-standard datasets to estimate accurate SV mutation rates at present. Notably, a study from Turner et al published during revision of this manuscript identified 88 de novo SVs from 476 of these quartets with an estimated 87.5% confirmation rate using microarray validation 31 .…”
Section: Resultsmentioning
confidence: 95%
“…Continuing the analogy, instead of candidate genes, the field would be substituting “candidate annotations” with all likelihood of poor outcomes, due to myriad combinations of annotations, cell types, brain regions, and developmental stages. Several ASD studies have selected different regions of the noncoding genome on which to focus 16,31,36,43,44 , and associations from initial small studies have failed to replicate in larger datasets (Supplementary Fig. 15), a trend likely to persist if nominal significance is the threshold chosen for exploring genomes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, results of two WGS studies analyzing the same dataset of the Simons Simplex Collection (>500 quads: a father, a mother, a proband with autism, and an unaffected sibling; probands carrying likely causal variants were excluded from the Pilot and Phase 1 batches) with an emphasis on non‐coding DNM were reported. One study (Turner et al …”
Section: Rapidly Expanding Knowledge On Functional Non‐coding Elementsmentioning
confidence: 99%
“…However, nominal significance was indeed observed in the control group, further suggesting need of a comprehensive, unbiased, and appropriately stringent approach, such as CWAS. Key findings and the points of difference in these two studies are summarized in Table …”
Section: Rapidly Expanding Knowledge On Functional Non‐coding Elementsmentioning
confidence: 99%
See 1 more Smart Citation